P668 Measured and modelled data suggest that oral administration of V565, a novel domain antibody to TNF-alpha, could be beneficial in the treatment of IBD. (16th January 2018) - Nurbhai, S; West, M; MacDonald, T; Parkes, G; Irving, P; Vossenkaemper, A; Crowe, S
Abstract: Background: V565 is a novel oral domain antibody (Vorabody) to TNF engineered to be resistant to intestinal proteases. Preclinically it demonstrated similar anti-TNF properties to adalimumab and infliximab. As previously reported it has minimal systemic absorption and is safe and well tolerated by human volunteers after high single and multiple oral doses. Clinical utility of V565 requires the ability to deliver therapeutic concentrations to inflamed areas in the GI mucosa. As measurement of concentrations within the human gut mucosa is difficult we developed a model, based on V565 degradation rates in ex vivo human ileal and faecal supernatants, to predict mucosal exposures. Methods: The model assumes synchronous tablet release from the stomach, divides the gut from duodenum to rectum into 110 equal volume segments, assumes mini-tablet dissolution occurs at three different times after dosing, applies different degradation rates to the small intestine and caecum + colon, and has a variable transit time. The model assumes Gaussian distribution of V565 after dissolution and that residual drug is degraded at a rate dependent on gut position. Potential V565 exposures in inflamed mucosa are calculated as a percentage of luminal [V565]. To verify the applicability of the model we compared the predicted luminal concentrations from the model to the actual concentrations measured in Phase 1 Crohn's volunteers given a single oral dose of V565. In addition fluorescent immunohistochemistry was used to detect V565 in the lamina propria (LP) of UC patients undergoing a pilot study. Results: According to the model 555 mg o.d. should result in a rectal mucosal [V565] of 372 nM assuming 5% transit from lumen. This concentration is well above the serum adalimumab nadir concentration for mucosal healing ( 55 nM) and should therefore exert a beneficial effect on inflammatory process. Measured faecal concentrations from 6 CD patients in the first human study were highly concordant with modelled data, with 12 of 14 measured concentrations being within a half-log of predicted. In the small UC study a dose of 555 mg tid for 7 days resulted in detection of V565 in the LP, and a reduction in inflammatory processes. Conclusions: Our model indicates that an oral dose of 555 mg o.d. should result in therapeutic concentrations in the mucosa. The model's utility is strongly supported by the similarity between measured and predicted stool concentrations, and the fact that oral dosing resulted in detection of V565 in colonic mucosa and reduction in inflammatory process. 1 Extrapolating the model suggests that lower doses should also be sufficient to maintain mucosal concentrations at therapeutic levels providing mucosal [V565] is 5% of luminal [V565]. Reference: 1. Nurbhai S, Parkes G, West M, et al. V565, a novel oral domain antibody to TNF, reduces colonic mucosal inflammation after 7 days oral dosing to patients with ulcerative colitis. UEGW Presentation LB05. 2017.